Thermochemistry of N‐heterocyclic carbenes with 5‐, 4‐, 3‐, and 2‐membered rings. Issue 10 (13th March 2014) - Altun, Zikri; Bleda, Erdi A.; Trindle, Carl; Wang, Jason
<x xml:space="preserve">Abstract</x> N‐heterocyclic carbenes (NHCs) based on imidazole‐2‐ylidene (1) or the saturated imidazolidine‐2‐ylidene (2) scaffolds are long‐lived singlet carbenes. Both benefit from inductive stabilization of the sigma lone pair on carbon by neighboring N atoms and delocalization of the N pi lone pairs into the nominally vacant p‐pi atomic orbital at the carbene carbon. With thermochemical schemes G4 and CBS‐QB3, we estimate the relative thermodynamic stabilization of smaller ring carbenes and acyclic species which may share the keys to NHC stability. These include four‐membered ring systems incorporating the carbene center, two trivalent N centers, and either a boron or a phosphorus atom to complete the ring. Amino‐substituted cyclopropenylidenes have been reported but three‐membered rings containing the carbene center and two N atoms are not known. Our calculations suggest that amino‐substituted cyclopropenylidenes are comparable in stability to the four‐membered NHCs but that diazacyclopropanylidenes would be substantially less effectively stabilized. Concluding the series are acyclic carbenes with and without neighboring N atoms and a series of "two‐membered ring" azapropadienenylidene cations of form :CNW with W = an electron‐withdrawing agent. We have studied W = NO2, CH2(+), CF2(+), and (CN)2C(+). Although these systems display a degree of stabilization and carbene‐like electronic structure, the stability of the NHCs is unsurpassed. © 2014 Wiley Periodicals, Inc.